Sexual Minority Status Disparities in Life's Essential 8 and Life's Simple 7 Cardiovascular Health Scores: A French Nationwide Population‐Based Study - Omar Deraz; Billy Caceres; Carl G. Streed; Lauren B. Beach; Xavier Jouven; Mathilde Touvier; Marcel Goldberg; Marie Zins; Jean‐Philippe Empana (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background A higher burden of cardiovascular disease risk factors has been reported in sexual minority populations. Primordial prevention may therefore be a relevant preventative strategy. The study's objectives are to estimate the associations of Life's Essential 8 (LE8) and Life's Simple 7 (LS7) cardiovascular health scores with sexual minority status. Methods and Results The CONSTANCES is a nationwide French epidemiological cohort study that recruited randomly selected participants older than 18 years in 21 cities. Sexual minority status was based on self‐reported lifetime sexual behavior and categorized as lesbian, gay, bisexual, or heterosexual. The LE8 score includes nicotine exposure, diet, physical activity, body mass index, sleep health, blood glucose, blood pressure, and blood lipids. The previous LS7 score included 7 metrics without sleep health. The study included 169 434 cardiovascular disease–free adults (53.64% women; mean age, 45.99 years). Among 90 879 women, 555 were lesbian, 3149 were bisexual, and 84 363 were heterosexual. Among 78 555 men, 2421 were gay, 2748 were bisexual, and 70 994 were heterosexual. Overall, 2812 women and 2392 men declined to answer. In multivariable mixed effects linear regression models, lesbian (β=−0.95 [95% CI, −1.89 to −0.02]) and bisexual (β=−0.78 [95% CI, −1.18 to −0.38]) women had a lower LE8 cardiovascular health score compared with heterosexual women. Conversely, gay (β=2.72 [95% CI, 2.25–3.19]) and bisexual (β=0.83 [95% CI, 0.39–1.27]) men had a higher LE8 cardiovascular health score compared with heterosexual men. The findings were consistent, although of smaller magnitudes for the LS7 score. Conclusions Cardiovascular health disparities exist in sexual minority adults, particularly lesbian and bisexual women, who may represent a priority population for primordial cardiovascular disease prevention.